Code Switching by English Students in Class Presentations - Ayu Panuntun, Ida; Hayati, Rizka (KnE Social Sciences, 2022)
For Indonesian students, learning English is learning a second language. Learning a second language is not easy for students, including those at Pekalongan University. They often become bilingual learners, inserting Indonesian into English conversations. This happens when they are involved in class presentations. The aim of this study was to describe the type of code switching used by English students in class presentations. The research design was descriptive qualitative. The data included 15 utterances from the speaker of each group in the class presentations. It was found that there were three types of code switching used by English students in class presentations. These were intrasentential (26.6%), intersentential (40%) and extrasentential (33.3%). Among the three types above, intersentential was the type of code switching most used by English students. Keywords: presentation, code switching, type of code switching